Integrasi Nilai Dakwah dan Pengabdian: Program Cukur Sunah KKN VIII STIBA Makassar di Desa Kurusumange: Integration of Da'wah and Community Service Values: The "Sunah Haircut" Program of KKN VIII STIBA Makassar in Kurusumange Village - Ahmad Syaripudin (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2025)
The Community Service Program (KKN) of STIBA Makassar, Batch VIII, was conducted in Kurusumange Village, Tanralili Subdistrict, Maros Regency, as a form of student dedication to the development of Islamic education. This program was initiated in response to the lack of sustainable religious guidance in the community. The study aims to describe the contributions of students through KKN programs designed based on a needs analysis of the community using the SOAR approach (Strengths, Opportunities, Aspirations, Results). The programs included the deployment of imams and Tarawih preachers during Ramadan, deployment of Friday khateebs, dawn lectures, short-term Islamic boarding schools (Pesantren Kilat), teaching at schools, Quran learning centers (TPA), adult Quran learning programs (DIROSA), social service activities, Lailatul Qadr Night Study Sessions (KMLQ), mosque cleaning campaigns (BBM), Sunnah-based haircuts and cupping therapy, and child-oriented programs such as GAS (Echo of Righteous Children). The results showed increased community participation and a growing religious spirit among various segments of the population. This KKN program had a positive impact on strengthening Islamic education in the village.